Biofilm formation and time course study on growth of saprophytic leptospira - Alia Diyana, binti Mohamed Hassim (Universiti Malaysia Sarawak (UNIMAS), 2016)
Leptospirosis is a zoonotic disease carried by animals especially rodent as the host caused by Leptospira that can be transmitted through contaminated environmental surface water. Leptospires exist as saprophytic organisms that are aquatic or as pathogen that are able to survive in water and other sources such as soil, and rat. The main aim for this study is to determine the relationship between contact time and biofilm formation of saprophytic Leptospira. A total of six saprophytic Leptospira strains were used in this study. Quantification of biofilm was done by crystal violet assay in 24-well plates for every 24 hour based on the value of optical density at 600 Mn. Saprophytic leptospires form biofilm from day 3 until day 5 with 1.916 as the highest optical density and correlate with colour intensity at the bottom of the well plates. Visualization of biofilm by phase-contrast microscopy of two representative saprophytic strain show a relationship with the data obtained and colour intensity of stained well plates. The current knowledge from this study helps for better understanding on contact time of biofilm formation by saprophytic Leptospira.